Age at onset in patients with Lennox-Gastaut syndrome: Correlations with clinical manifestations. (June 2022) - Asadi-Pooya, Ali A.; Farazdaghi, Mohsen
Highlights: In 10 patients (3%), LGS started at age 14 years or above. Intellectual disability was less frequent in those with an older age at onset. Tonic-clonic seizures were more frequent in those with an older age at onset. Abstract: The aim of the current study was to investigate the age at onset in patients with Lennox-Gastaut Syndrome (LGS). We also investigated the clinical and EEG characteristics of these patients in different age groups. This was a retrospective study. All patients with a diagnosis of LGS were recruited at the outpatient epilepsy clinic at Shiraz University of Medical Sciences, Shiraz, Iran, from 2008 through 2020. 300 patients had LGS. Age at onset was 3.3 ± 4.1 years (minimum = 0 and maximum = 21 years). In 10 patients (3%) LGS started at age 14 years or above. Epileptic spasms were more often observed in those with an age at onset below one year (8%) compared with those with an age at onset of 1 to 8 years (0.7%) [Odds Ratio (OR) = 10.32]. Intellectual disability was less frequently observed in those with an age at onset of 8 years and above (68%) compared with those with an age at onset of 1 to 8 years (90%) (OR = 0.33). Tonic-clonic seizures were more often observed in those with an age at onset of 8 years and above (83%) compared with those with an age at onset of 1 to 8 years (55%) (OR = 2.87). While age at onset of LGS in the majority of patients is below 8 years, in some patients the syndrome begins in their late childhood or even during adolescence. Age at onset of LGS has significant correlations with the clinical manifestations of the syndrome.